Out of Water : Design Solutions for Arid Regions - Margolis, Liat; Chaouni, Aziza (Birkhäuser, 2014)
Water scarcity is becoming increasingly familiar to us. Although access to water resources is an issue of global concern, arid climates are where necessity begets inventions that may serve as examples for action or prevention across a multitude of climate zones and geographies. In facing the prevalence of water scarcity across the globe, due to a mix of climatological and man-made factors, the question we must ask ourselves today is Water for What? Which approaches can landscape, urban and architectural designers take in order to apply their specific professional skills and means? What potential do available technologies and materials offer, and what methods and tools can be derived from social engagement? Based on five years of research, the preparation of and feedback on a traveling exhibition, as well as a major conference, the results of the Out of Water project are laid out here in a series of case studies and essays by international experts, including analytical drawings of both projected and implemented solutions.